Epiluminiscenčna mikroskopija v diagnostiki nejasnih melanocitnih kožnih spreemb: primerjava dermatoskopskih ABCD pravil z novo sedem točkovno listo preverjanja, ki temelji na analizi vzorcev - Argenziano, Giusseppe (Radiology and oncology (Ljubljana), 1999)
Objective: To compare the reliability of a new seven-point checklist based on a simplified epiluminescence microscopy (ELM) pattern analysis with the ABCD rule of dermatoscopy and standard patern analysis for the diagnosis of clinically doubtful melanocitic skin lesions. Design: In a blind study ELM images of 342 histologically proven melanocytic skin lesion were evaluated forthe presence of 7 standard criteria that we called "ELM seven-point checklist". For each lesion "overal"l and "ABCD scored" diagnoses were recorded. From a training set of 57 melanomas and 139 atypical nonmelanomas, odds ratios were calculated to create a simple diagnostic model based on identification of major and minor criteria for the "seven-point scored" diagnosis. A test set of 60 melanomas and 86 atypical nonmelenomas wasused formodel validation and was presented to two less experienced ELM observers, who recorded the ABCD and seven-point scored diagnoses. Setting: University Medical Centers. Patients: A sample of subjects with excised melanocytic lesions. Main outcome measures: Sensitivity, specificity, and accuracy of the models for diagnosing melanoma. Results: From the total combined sets the seven-point checklist gave a sensitivity of 95% and specificity of 75%, compared with 85% sensitivity and 66% specificity using ABCD rule, and 91% sensitivity and 90% specificity using standard pattern analysis (overall ELM diagnosis). Compared with ABCD rule, the seven-point meethod allowed less experienced observers to obtain higher diagnostic accuracy values. Conclusions: The ELM seven-point checklist provides a simplification of the standard pattern analysis becauseof the low number of features to identify andthe scoring diagnostic system. (Abstract truncated at 2000 characters.)
Keywords: Diagnosis; Luminescence; Melanoma; Nevus, pigmented; Pathology; Skin neoplasms